Application of The 7p Mix Marketing on Patient Satisfaction at Hospitals - Muliawati Mutia; Pujianto Pujianto (Malahayati Nursing Journal, 2022)
ABSTRACT Hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. In addition, the Hospital also carries out a business mission to earn profit and ensure the sustainability of its business. The marketing mix is a hospital strategy to maximize service delivery to clients. This study aims to analyze the effect of the 7P's marketing mix (product, price, place, promotion, process, people, physical building) on patient satisfaction in hospitals. Literature review is used for research methods, the initial step in determining the topic, the keywords used, Science Direct, Pro Quest, Google Scholar dan Elsevier are the database journals used. Reference search is limited from 2016 to 2020. The keywords used are “Marketing Mix 7p, Hospital, Patient Satisfaction”. Research references found there are 65 studies. A total of 55 articles were excluded and 10 articles were included in the discussion. Selection journals were selected based on inclusion criteria. The inclusion criteria in this study were the analysis of the influence of the 7P Marketing Mix on Patient Satisfaction in Hospitals. Based on the 5 studies reviewed, one study explained that the 7P marketing mix had a significant effect on patient satisfaction through statistical tests with p value = 0.00 = 0.05. The level of patient satisfaction affects the optimal marketing of the 7Ps. Keywords: Marketing Mix, Marketing Mix 7P, Hospital Patient Satisfaction